APAKAH PENGUNGKAPAN CSR, KEPUTUSAN INVESTASI, DAN UKURAN PERUSAHAAN MERUPAKAN FAKTOR DETERMINAN NILAI PERUSAHAAN? - Clarissa Nadine Limanda; Luky Patricia Widianingsih (Media Akuntansi dan Perpajakan Indonesia, 2023)
This study aims to determine the effect of CSR disclosure, investment decisions, and company size on firm value. The research was conducted at consumer non-cyclical sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019–2021. This research method is quantitative and analyzes statistical data through Eviews software. This study uses secondary data sources. The measurement scale in this study is the nominal scale (CSR disclosure and company size) and the ratio scale of investment decision and firm value). The sampling technique used purposive sampling. The samples obtained based on the criteria are 66 companies. The data analysis method used is multiple linear regression analysis. The results of this study indicate that CSR disclosure proxied by the presence of sustainability report (SR) disclosures has an effect on firm value, investment decisions proxied by total assets growth (TAG) have no effect on firm value, and firm size proxied by ln total assets has an effect negative to company value.